The isolated carboxy‐terminal domain of human mitochondrial leucyl‐tRNA synthetase rescues the pathological phenotype of mitochondrial tRNA mutations in human cells. Issue 2 (10th January 2014) - Perli, Elena; Giordano, Carla; Pisano, Annalinda; Montanari, Arianna; Campese, Antonio F; Reyes, Aurelio; Ghezzi, Daniele; Nasca, Alessia; Tuppen, Helen A; Orlandi, Maurizia; Di Micco, Patrizio; Poser, Elena; et al.
Synopsis <boxed-text content-type="graphic" id="emmm201303198-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Non‐cognate mitochondrial aminoacyl‐tRNA syntethases improve viability and bionergetic proficiency of human cells with pathogenic mutations in the mt‐tRNAIle gene. The isolated carboxy‐terminal domain of human mt‐leucyl tRNA synthetase improves the pathologic phenotype. Mitochondrial aminoacyl‐tRNA syntethases (mt‐aaRSs) can rescue the pathologic phenotype of human cells carrying mutations, both in cognate and non‐cognate mitochondrial tRNAs. The carboxy‐terminal domain of mt‐leucyl syntethase (mt‐LeuRS Cterm) is sufficient to exert the rescuing effect, even more efficiently than the whole enzyme. In line with its rescuing effect, mt‐LeuRS Cterm is imported within mitochondria, even in absence of a canonical mt import sequence.